INSTAGRAM SEBAGAI MEDIA DAKWAH (STUDI KASUS INSTAGRAM @PEMUDAHIJRAH) - Aliffiani Ayu Nurrohmah; Ahmad Nurcholis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
Abstract Preachers nowadays have used social media (social media) to spread their da'wah. The Pemuda Hijrah Instagram account is an account that spreads da'wah content by making videos about da'wah, providing Islamic studies with the theme of inviting young people to emigrate and improve themselves. With the title